Teknik Penerjemahan Onomatope Gitaigo dalam Novel Funiculi Funicula Before The Coffee Gets Cold - B.S. Maturbongs, Winona Raissa; Taqdir, Taqdir; Kasmawati, Kasmawati (Vocational College of Diponegoro University, 2024)
This study focuses on onomatopoeia of gitaigo. The aim of this study is to find out the types of gitaigo in the novel Funiculi Funicula Before the Coffee Gets Cold and the translation techniques of gitaigo used in the novel. This study uses descriptive qualitative method. The study data were collected by reading the novel Funiculi Funicula Before the Coffee Gets Cold. The data analyzed using Hinata & Hibiya's (1989) theory on gitaigo and Molina and Albir's (2002) theory on translation techniques. The research found 131 gitaigo onomatopoeias, which are 21 gijou, 54 gitai, and 56 giyou. In terms of translation techniques, nine techniques were found, including amplification, description, discursive creation, common equivalence, generalization, literal translation, particularization, reduction and modulation.